A look at foreign direct investment in China: 2004–2012. (2018) - Dutta, Amitabh S.; Patel, Shama; Perez, Enrique M.
This study examines the foreign direct investment (FDI) in China over the period 2004–2012. The motivation behind the study was to see if the 2008 financial crisis had an impact on the levels of FDI being allocated to China from different countries. The data was divided into two sub-periods of four years each, 2004–2007 and 2009–2012. There was FDI data available for 16 geographic areas around the globe. This study finds that 12 of 16 regions/countries tested show no significant differences in their average pre- and post-2008 levels of FDI in China. Developing economies as a whole, the regions of East Asia and South East Asia and the country of Singapore all show significantly higher levels of FDI in China after the global financial meltdown.